Digital ecosystem model of the agro-industrial complex - D. A. Korobeinikov (Вестник университета)
The study is devoted to modelling a sectoral ecosystem for the agro-industrial complex, incorporating into a single platform solution tools and mechanisms for the interaction between sectoral business structures in value chains as well as the proactive implementation of government functions for managing and supporting the industry. The ecosystem architecture has been developed and structured in terms of organizational, infrastructure, innovation, communication and logistics components. The role of the system actor and IT integrator is assigned to the Ministry of Agriculture of the Russian Federation. The main and additional functions of the digital platform are highlighted. A description of its product and service segments is provided. The options for implementing the process subsystem on the Gostech and GosOblako platforms as well as the Russian Agricultural Bank platform are assessed, the advantages of each solution presented. The importance of involving the research potential of departmental high education institutions and research institutes in the development of the ecosystem’s service segment is substantiated.